ETOS BELAJAR SANTRI DI PESANTREN AL ISTIQOMAH BANJARMASIN - Sigit Ruswinarsih (Universitas Lambung Mangkurat, 2013)
This research discusses about santri’s learning ethos in Pesantren Al Istiqamah. In theoretical aspect, this research might be able to increase our knowledge in social studies education. Practically,this research can be studied as the materials to understand and develop the santri’s characters in facing a more innovative education, the result of this research can be used in understanding the santri/students’ characters so that they can plan a more effectivelearning, the result of this research can be as a reference to establish their attitudes in learning, also this research can be used as input in organizing children’s education in family environment.This research location is Pesantren Al Istiqamah, Pemurus Baru Sub-district, South Banjarmasin District, Banjarmasin City,South Kalimantan Province.The conclusions of this research are (1) santri interprets the meaning of learning in two dimensions those are earthly and hereafter dimension, (2) santri’s learning motivation includes motivation that is based on its source, those are intrinsic and extrinsic motivation.Keywords: Learning Ethos, Santri, Pesantren